Effectiveness of Yoga, Fast of Dawood, Green Tea and Apple Juice as Suppressors of PPAR-γ, C/EBP-α, and SREBP-c for Management of Obesity on Adolescents - Lutfian Lutfian; Aris Munandar; Rismawan Adi Yunanto; Ahmad Rizki Nur Hakiki (Nursing and Health Sciences Journal (NHSJ), 2021)
Obesity is a condition that can increase the risk of some diseases such as reduced brain capacity, dyspnea, skin irritation, hypertension, and diabetes. Proper treatment is needed to overcome the problems of obesity. The objective of this study was to investigate the effectiveness of Yoga, fast of Dawood, Green Tea, and Apple juice to suppressor PPAR-γ gene activity, C / EBPα, and SREBP-c to manage obesity in adolescents. The method used in this study was a literature review from journal publications through the database ScienceDirect, PUBMED, and google scholar, and the criteria were Indonesian and English with a range of publication years 2014-2019. Nine main articles were used as references in this study. These articles proved that yoga therapy could maintain the balance and health of the physical, emotional, and spiritual dimensions, and Fast of Dawood can limit the amount of calorie intake at a particular time. Moreover, by consuming green tea as a source of polyphenol derivatives and apples with high of flavanol, anthocyanidin, dihydrochalcones, and hydroxycinnamic acid could decrease adolescents' body weight. Yoga and Fast of Dawood exercise can reduce adipogenesis and induce reverse cholesterol transport, cellular cholesterol released, reduced pro-inflammatory cytokines dan decreased the incidence of obesity.